2006
DOI: 10.1111/j.1365-2052.2006.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Globally dispersed Y chromosomal haplotypes in wild and domestic sheep

Abstract: To date, investigations of genetic diversity and the origins of domestication in sheep have utilised autosomal microsatellites and variation in the mitochondrial genome. We present the first analysis of both domestic and wild sheep using genetic markers residing on the ovine Y chromosome. Analysis of a single nucleotide polymorphism (oY1) in the SRY promoter region revealed that allele A-oY1 was present in all wild bighorn sheep (Ovis canadensis), two subspecies of thinhorn sheep (Ovis dalli), European Mouflon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 44 publications
5
92
1
Order By: Relevance
“…Several studies have shown that H6 is the most predominant haplotype in different sheep breeds (12,14,(23)(24)(25), except for the Tyrolean Mountain sheep (Austria) and Brown and White Mountain sheep (Germany) that exhibited only the H8 haplotype (12). In this regard, African breeds also showed a higher frequency for the H6 haplotype (66.6%) (13), while in this study the H8 haplotype is the most frequently observed (55.5%).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Several studies have shown that H6 is the most predominant haplotype in different sheep breeds (12,14,(23)(24)(25), except for the Tyrolean Mountain sheep (Austria) and Brown and White Mountain sheep (Germany) that exhibited only the H8 haplotype (12). In this regard, African breeds also showed a higher frequency for the H6 haplotype (66.6%) (13), while in this study the H8 haplotype is the most frequently observed (55.5%).…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, this haplotype was found in the Western Thin Tail. The H5 haplotype has been observed in European (19%) and Australian (27.2%) sheep (13), as well as in Asian and Caribbean (12,13) breeds, but it was absent in all African breeds analyzed so far. In this study, this haplotype was detected only in the Black Thibar breed, which could be explained by the (Figure 2), suggesting possible genetic admixture as a result of uncontrolled reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsatellites are used, in livestock species for estimating genetic variation within and among breeds (Buchanan et al, 1994;Cronin et al, 2009;Diez-Tascon et al, 2000a;Dowling et al, 2008;Schmid et al, 1999;Saitbekova et al, 1999), for admixture studies (Alvarez et al, 2004;Freeman et al, 2004Freeman et al, , 2006MacHugh et al, 1997;Vicente et al, 2008) and for assigning individuals to breeds (Baumung et al, 2006;Cornuet et al, 1999;Maudet et al, 2002;Meadows et al, 2006;Troy et al, 2001). …”
Section: Analysis Of Genetic Variation In Animalsmentioning
confidence: 99%